"A Fair Boy, Certain, but a Fool to Love Himself": Queer Reflections of the Myth of Narcissus in Shakespeare and Fletcher's The Two Noble Kinsmen. (2nd January 2020) - Ball, Hilary
ABSTRACT: It has been widely noted that The Two Noble Kinsmen dramatises the erasure of same-sex desire as tragic, and that the play's structural drive toward a comic ending is accompanied by a poignant sense of loss. Building on previous queer readings of The Two Noble Kinsmen, this paper examines the apparent equality and even similarity of the play's potential same-sex lovers, for whom looking at each other is like looking in a mirror. I argue, however, that the playwrights are not participating uncritically in what Valerie Traub has identified as the early modern discourse of "erotic similitude", whereby homoerotic desire is attributed to Narcissus-like attraction to sameness. Rather, despite various characters' and critics' insistence on the kinsmen's indistinguishability, I demonstrate that from the beginning Palamon and Arcite are animated by distinct drives – toward individualism on Palamon's part, and toward imitation on Arcite's. By examining Shakespeare and Fletcher's direct and indirect use of the Ovidian Narcissus myth, moreover, I highlight the ways in which Kinsmen both invokes and undermines early modern tropes and images associated with erotic similitude, thus staging an alternative paradigm of same-sex desire, one founded on difference rather than sameness.